Kimbanguism : An African Understanding of the Bible - Mokoko Gampiot, Aurelien (Book collections on Project MUSE., 2017)
From the early days of Christianity in Sub-Saharan Africa, a Eurocentric view of Christian teaching was a primary tool in the subjugation and domination of native populations. Since 1921 Kimbanguism, an African Initiated Church, has advocated a reconstruction of Blackness by appropriating the parameters of Christian identity. The prophet Simon Kimbangu, the founder of the movement, has inspired 17 million followers with Pan-African messages of political and spiritual liberation. The Spurned Race is the first comprehensive study of Kimbanguism since the pioneering books of the 1980s. The son of a Kimbanguist pastor, Gampiot uses his inside resources to offer new sociological and theological analyses of the church's interpretation of and signification on the Christian bible. The Spurned Race provides a unique and important look at the independent nature of early African Christian prophetic movements.